Perbedaan Kecemasan antara Kecerdasan Emosi Tinggi dan Kecerdasan Emosi Rendah pada Mahasiswa Angkatan 2010 yang Menghadapi Skripsi di Fakultas Kedokteran UNS - Adinda Ferinawati; Yusvick M. Hadin; Lilik Wijayanti (Nexus Kedokteran Klinik, 2014)
Background: Anxiety is a state of excessive tension or inappropriate tension which is characterized by feelings of worry, uncertainty, or fear. Anxiety can be overcome with good emotional intelligence. Of the five areas that exist in emotional intelligence, self recognizing and managing emotions are the aspects who have a big role to overcome anxiety. This study aimed to determine whether there is a difference of anxiety between high emotional quotient and low emotional quotient of students year of 2010 doing mini thesis in Medical Faculty of UNS. Method: This research was an analytical descriptive research using cross sectional approach. The subjects were Medical Faculty students year of 2010 of Sebelas Maret University. Data were collected by using purposive sampling method within inclusion and exclusion criterias. Emotional quotient was measured by Emotional Quotient questionnaire, while anxiety was measured by Taylor Manifest Anxiety Scale. For assesing and finding honesty in answering questions given, was used L-MMPI scale questionnaire. Sixty samples were obtained and analyzed using Chi-Square test through SPSS 20.0 version for Windows program. Result: The result of research showed that 23 students (76.7 %) who have low emotional quotient were feeling anxious and 7 students (23.3 %) who have low emotional quotient were not feeling anxious. While 9 students (30 %) who have high emotional quotient were feeling anxious and 21 students (70 %) who have high emotional quotient were not feeling anxious. Chi-Square test showed the result of p = 0.000 and Odds Ratio = 7.667. Conclusion: There is a significant difference of anxiety between high emotional quotient and low emotional quotient of students year of 2010 doing mini thesis in Medical Faculty of UNS. Keywords: Anxiety, emotional quotient, students doing mini thesis